Bioaccessibility of folic acid in egg white nanocarriers and protein digestion profile in solution and in emulsion - Arzeni, Carolina (2019)
The objective of this work is to assess bioaccessibility of folic acid in egg white (EW) nanocarriers after digestion of solutions and emulsions containing the vitamin-protein complexes. Furthermore, the influence of folic acid binding on the peptides profile after digestion is also evaluated. To this end an in vitro gastrointestinal digestion was performed and the pattern of digestion products was determined by high performance liquid chromatography. When folic acid was bound to nanocarriers, the vitamin peak area was approximately 80% lower than the one for folic acid alone. In emulsion, even less amount was detected. After digestion, no significant differences on folic acid peak areas were observed. Folic acid was released from nanocarriers after digestion, thus indicating that the vitamin would be bioaccessible in the site of absorption. Moreover, it was demonstrated by tricine-SDS-PAGE that folic acid binding induced a slight aggregation of proteins, although it did not alter the profile of peptides obtained after digestion. Binding of folic acid to nanocarriers proved to cause no negative effect on EW proteins digestibility. On the contrary, it seemed to slightly enhance their digestion. These nanocarriers would constitute an adequate system for the preservation, transport and target delivery of this bioactive.